1988
DOI: 10.1063/1.455188
|View full text |Cite
|
Sign up to set email alerts
|

Infrared diode laser spectra of MgH and MgD (X 2Σ+)

Abstract: Infrared absorption spectra of magnesium hydride in its 2Σ+ ground state have been measured at Doppler limited resolution in a dc discharge of hydrogen over magnesium. Most of the transitions arise from the fundamental bands of 24MgH and 24MgD, but, in addition, a few lines attributable to 25Mg and 26Mg species have been detected, as well as v=2←1 hot band transitions in 24MgH and 24MgD. Most of the lines are characterized by a doublet splitting due to the electron spin–rotation interaction (γN⋅S) which helps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 10 publications
3
35
0
Order By: Relevance
“…The available diode laser infrared spectra 27 contain lines from the vϭ1←0 and vϭ2←1 bands of MgH and MgD with an experimental uncertainty of 0.002 cm Ϫ1 , and there is no systematic discrepancy between those lines and our calibrated line positions. We included the diode laser infrared lines and all pure rotational lines 24 -26,28 in our data set.…”
Section: Results and Analysismentioning
confidence: 58%
See 3 more Smart Citations
“…The available diode laser infrared spectra 27 contain lines from the vϭ1←0 and vϭ2←1 bands of MgH and MgD with an experimental uncertainty of 0.002 cm Ϫ1 , and there is no systematic discrepancy between those lines and our calibrated line positions. We included the diode laser infrared lines and all pure rotational lines 24 -26,28 in our data set.…”
Section: Results and Analysismentioning
confidence: 58%
“…To minimize the number of digits required to accurately reproduce the data, the fit to determine the constants of Tables I and II applied the sequential rounding and refitting procedure, 34 starting from the highest order parameter of the highest observed vibrational level. The new band constants for the vϭ0 levels of 24 MgH and 24 MgD are compared with the constants previously determined from the diode laser infrared 27 and pure rotational spectra, 26,28 in Table III. Note, however, that we have determined a set of band constants for the vϭ0 to 4 levels of 24 MgH and the vϭ0 to 5 levels of 24 MgD, while the previous diode laser infrared data included only the vϭ0 to 2 levels.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The 7 and the 12 /mi lines were identified from theory as the 5g-6h, 6g-lh, and 6h-7i transitions of neutral magnesium (Chang & Noyes 1983). The identifications of the 12 /mi lines were confirmed by laboratory diode laser absorption spectroscopy (Lemoine, Demnynk, & Destombes 1988). Additional midinfrared lines of Mg i have also been noted in the solar spectrum (Chang & Noyes 1983;Chang 1987;Glenar et al 1988;Jefferies 1991) and confirmed in laboratory spectra (Lemoine et al 1990).…”
Section: Introductionmentioning
confidence: 79%